PENERAPAN SKEPTISME PROFESIONAL AUDITOR INTERNAL PEMERINTAH DALAM MENDETEKSI KECURANGAN DI SEKTOR PUBLIK (STUDI PADA AUDITOR DI BPKP PERWAKILAN PROVINSI JAWA TIMUR) - Rima Novi Kartikasari; Gugus Irianto; Yeney Widha Prihatiningtias (Jurnal Akuntansi Aktual, 2017)
This research is aimed to describe the application of professional skepticism by auditor in BPKPRepresentative in East Java to detect. The approach used in this research is a qualitative descriptive usingcase study. Data collected through interviews to the informant using snowball method. The application ofprofessional skepticism would be understood based on its characteristics as stated by Hurtt (2010). Theresults showed that the auditor in BPKP Representative East Java apply professional skepticism at eachstage of the audit to detect public sector’s fraud. This is reflected in the way of critical thinking whenauditors understanding a fraud case, the suspention of judgment in decision making, make a reasonableassurance by searching knowledge and understanding the other related, and have a self-motivation and selfconfidence. Characteristics of skepticism can be formed from a trait, level of experience, and a state. Theimplication of this research is to increase auditor’s attention to apply professional skepticism and toconsider the characteristics of skepticism when planning an assignment.Keywords:professional skepticism, government’s internal auditor, detection, public sector’s fraud, qualitativedescriptive